A functionally significant polymorphism in ID3 is associated with human coronary pathology. - Ani Manichaikul; Stephen S Rich; Heather Perry; Joseph Yeboah; Michelle Law; Molly Davis; Matthew Parker; Michael Ragosta; Jessica J Connelly; Coleen A McNamara; Angela M Taylor (PLoS ONE)
Aims We previously identified association between the ID3 SNP rs11574 and carotid intima-media thickness in the Diabetes Heart Study, a predominantly White diabetic population. The nonsynonymous SNP rs11574 results in an amino acid substitution in the C-terminal region of ID3, attenuating the dominant negative function of ID3 as an inhibitor of basic HLH factor E12-mediated transcription. In the current investigation, we characterize the association between the functionally significant polymorphism in ID3, rs11574, with human coronary pathology. Methods and results The Multi-Ethnic Study of Atherosclerosis (MESA) is a longitudinal study of subclinical cardiovascular disease, including non-Hispanic White (n = 2,588), African American (n = 2,560) and Hispanic (n = 2,130) participants with data on coronary artery calcium (CAC). The Coronary Assessment in Virginia cohort (CAVA) included 71 patients aged 30-80 years, undergoing a medically necessary cardiac catheterization and intravascular ultrasound (IVUS) at the University of Virginia. ID3 SNP rs11574 risk allele was associated with the presence of CAC in MESA Whites (P = 0.017). In addition, the risk allele was associated with greater atheroma burden and stenosis in the CAVA cohort (P = 0.003, P = 0.04 respectively). The risk allele remained predictive of atheroma burden in multivariate analysis (Model 1: covariates age, gender, and LDL, regression coefficient = 9.578, SE = 3.657, p = 0.0110; Model 2: covariates Model 1, presence of hypertension, presence of diabetes, regression coefficient = 8.389, SE = 4.788, p = 0.0163). Conclusions We present additional cohorts that demonstrate association of ID3 SNP rs11574 directly with human coronary artery pathology as measured by CAC and IVUS: one a multiethnic, relatively healthy population with low levels of diabetes and the second a predominantly White population with a higher incidence of T2DM referred for cardiac catheterization.